KEMAMPUAN PENALARAN MATEMATIKA SISWA MA DENGAN METODE PROBLEM-BASED LEARNING - Samsul Hadi (LPPM Institut Pendidikan Nusantara Global, 2021)
The purpose of this study is to analyze the description of the mathematical reasoning ability of MA students in problem-based learning (PBM). This research uses a case study-based qualitative approach and was conducted in private madrasah aliyah in Central Lombok district. The number of participants in the study were 32 students of class X IPA even semester 2020/2021. Data was collected by means of tests (mathematical reasoning skills) and non-tests (interviews, observations, and documentation studies) to determine the mathematical reasoning abilities of MA students in problem-based learning. The result of this research is the mathematical reasoning ability of MA students in problem-based learning is included in the good category.